2021
DOI: 10.3389/fonc.2021.737547
|View full text |Cite
|
Sign up to set email alerts
|

Germline Mutation Landscape and Associated Clinical Characteristics in Chinese Patients With Renal Cell Carcinoma

Abstract: BackgroundRenal cell carcinoma (RCC) is a disease of genomic alterations, of which the complete panorama helps in facilitating molecular-guided therapy. Germline mutation profiles and associated somatic and clinical characteristics remains unexplored in Chinese RCC patients.MethodsWe retrospectively profiled the germline and somatic mutations of 322 unselected RCC patients using a panel consisting of 808 cancer-related genes. We categorized patients into three groups based on germline mutation status and compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 42 publications
0
9
2
Order By: Relevance
“…Consistent with prior reports, 10,24 we detected germline alterations at the highest frequency in CHEK2 and FH. Unlike other reports of Asian patients that demonstrate a comparable frequency in germline alterations in patients with RCC, 25,26 our rate of germline alterations in EAS (7%) and SAS (0%) was low.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Consistent with prior reports, 10,24 we detected germline alterations at the highest frequency in CHEK2 and FH. Unlike other reports of Asian patients that demonstrate a comparable frequency in germline alterations in patients with RCC, 25,26 our rate of germline alterations in EAS (7%) and SAS (0%) was low.…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with prior reports, 10,24 we detected germline alterations at the highest frequency in CHEK2 and FH . Unlike other reports of Asian patients that demonstrate a comparable frequency in germline alterations in patients with RCC, 25,26 our rate of germline alterations in EAS (7%) and SAS (0%) was low. TCGA analyses have indicated a lower rate of somatic VHL and PBRM1 in AFR patients compared with EUR patients, with a continuous trend based on the size of GA fraction of these ancestries 9,27 .…”
Section: Discussioncontrasting
confidence: 99%
“…However not all the CSGs harbouring a PGV were known to be associated with predisposition to RCC (only 4.5% of all cases had a PGVs in a CSG (VHL, FLCN, MET, TSC1/2, FH, SDHA/B/C/D, BAP1 and CHEK2) recognised as being associated with RCC predisposition) [18]. Other studies have reported a similar overall frequency of PGVs in RCC CSGs [17,42]; and higher frequencies (~9%) have been reported in case series in which ascertainment has been biased towards early onset and/or advanced stage RCC [43,44]. An extensive genomic analysis focusing on MPRT has not yet been performed within published series of unselected RCC but estimates of the diagnostic yield in MPRT have varied between 7% and 29%, [44,45].…”
Section: Discussionmentioning
confidence: 96%
“…Among the 18 VHL patients with LDs who were identified using NGS, 11.1% (2 of 18) had other germline mutations. In a recent study, 42.9% (3 of 7) of patients with VHL disease were identified to simultaneously harbour other germline mutations 31. In addition, some case reports have shown that patients with VHL germline mutations could harbour some other germline mutations such as DM1 mutations, CPT2 mutations, Xp11.2 translocations/TFE3 gene fusion and TMEM 127 mutations 32–35.…”
Section: Discussionmentioning
confidence: 99%